Taxonomic significance of leaf epidermis in tribe Trifolieae L. (Leguminosae; Papilionoideae) in Pakistan. (4th May 2019) - Rashid, Neelam; Zafar, Muhammad; Ahmad, Mushtaq; Khan, Mir Ajab; Malik, Khafsa; Sultana, Shazia; Shah, Syed Nasar
Abstract: Leaf epidermal anatomy of tribe Trifolieae L. has been studied with the objective to assess the characteristics that can be used to reevaluate the circumscription and systematic position of tribe. Using light and scanning electron microscopy, leaf epidermal characters of 17 species belonging to four genera of Trifolieae ( Medicago L., Melilotus Mill., Trifolium L. and Trigonella L.) are investigated. The placement of Melilotus and Trigonella in one section Grammocarpus was also reassessed on the basis of leaf epidermal characters. Presence of characteristic anomocytic stomata with great variation of size and short, unbranched, unicellular, non glandular trichomes with acute apex are diagnostic characters for delimitation of species in Trifolieae . The distributional density of trichomes varies greatly between genera and found to be highest in genus Medicago . The value of stomatal index ranges between 24.6% ( Trifolium dubium ) to 83% ( Trigonella foeno graceum ). In general, present study concludes that the variations of all traits are mostly sustained and intrinsic to the species and of promising taxonomic value. The combination of leaf epidermal characters in correlation with other traits has potential for taxonomic resolution at species level. Further phylogenetic studies on tribe, based on more comprehensive sampling will probably explain intrageneric relationships in Trifolieae . Abstract :